Study on the Extraction of Uranium by Tetraphenylphosphonium Chloride (TPPC) - KATSURA, K.; SHINAGAWA, M. (Journal of the Atomic Energy Society of Japan / Atomic Energy Society of Japan, 1960)
For the purpose of using TPPC (Tetraphenylphosphonium Chloride) as an extraction reagent, uranyl ion was changed to the complex anion by benzoic acid. Tetraphenylphosphonium uranyl tribenzoate is extracted into chloroform layer from the buffer solution containing benzoic acid and sodium benzoate. This paper described following subjects; (1) Proportionality between polarographic diffusion current and uranium concentration (2) lnterference of several ions on the extaction of uranium (3) Effects of TPPC concentration on the percentage extraction of uranium and the ratio of uranium to TPPC (4) lnvestigation of the optimum pH (5) Effects of the concentration of the complexing agent on the percentage extraction of uranium (6) Percentage extraction of Fission Products and the other raio active elements The result gave a good method for the seperation of uranium with TPPC.